Ethiopia: Analyzing the patterns of herd mobility - Homann-Kee Tui, Sabine; Rischkowsky, Barbara A. (Technical Centre for Agricultural and Rural Cooperation, 2005)
Sabine Homann and Barbara Rischkowsky explain how studying past and present herd mobility patterns can improve land management in the Borana lowlands.